At the dawn of delegation? Experiences and attitudes of general practitioners in Germany – a questionnaire survey - Katja Goetz; Anna Kornitzky; Janis Mahnkopf; Jost Steinhäuser (BMC Family Practice, 2017)
Abstract Background In the future, ‘delegation’ as task shifting from general practitioners (GPs) to non-physicians will be important in primary care. Therefore, the aim of this study was to evaluate the attitudes towards the concept of task shifting and to identify predictors of a positive attitude towards task shifting from the perspective of GPs. Methods This cross-sectional questionnaire study analysed attitudes towards the concept of task shifting and delegated tasks from the perspective of GPs who were recruited in the German federal state of Schleswig-Holstein. Descriptive statistics and binary regression analyses were computed to identify potential predictors of a positive attitude towards task shifting. Results Out of 1538 questionnaires distributed, 577 GP questionnaires were returned (response rate: 37.5%). A total of 53.2% of the respondents were male, and 37.3% were female. A positive attitude regarding task shifting was shown by 49% of the participating GPs. The highest level of agreement (95.2%) was found for time savings with task shifting, and a lower agreement (39%) was found regarding the lack of clarity concerning the responsibilities and legal aspects with regards to task shifting. The most frequently delegated tasks were recording electrocardiograms and measuring blood glucose levels. A positive attitude towards task shifting was positively associated with higher job satisfaction and a need for qualified staff. Conclusion Our sample of GPs for this study was very open-minded towards the concept of task shifting. Germany is just beginning this delegation, but the implementation of task shifting depends on different aspects, such as legal requirements, adequate payment and qualified staff. Finally, there is a need for continuing professional development in primary care teams, especially for non-clinical practice staff.